2012
DOI: 10.3917/spub.124.0329
|View full text |Cite
|
Sign up to set email alerts
|

La couverture vaccinale des adultes : enquêtes dans quatre populations d'Isère (France), 2002-2003

Abstract: In order to assess their vaccination policy, the public health authorities in Isère (France) conducted several surveys to determine the vaccination coverage rate among adults. In France, the current state of knowledge in this area is limited. Four separate surveys were conducted in 2002-2003: (1) a telephone survey of 976 adults, 18% of whom had vaccination certificates; (2) a survey of 44 general practitioners (805 patients); (3) a survey of occupational health centers (82 practitioners and 1,119 employees); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
2
2
0
1
Order By: Relevance
“…In our study, in the univariate analysis, only age and sufficient information about vaccination were associated with up-to-date vaccination (older patients were less likely to be up-to-date with their vaccinations), but age was not significant in the multivariable analysis, perhaps due to a lack of statistical power ( Table 4 ). These data are consistent with previous reports [ 6 , 7 , 8 , 9 ]. However, in contrast to previous studies, sex was not found to be significantly associated with vaccination status Table 4 [ 6 , 7 , 8 ].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In our study, in the univariate analysis, only age and sufficient information about vaccination were associated with up-to-date vaccination (older patients were less likely to be up-to-date with their vaccinations), but age was not significant in the multivariable analysis, perhaps due to a lack of statistical power ( Table 4 ). These data are consistent with previous reports [ 6 , 7 , 8 , 9 ]. However, in contrast to previous studies, sex was not found to be significantly associated with vaccination status Table 4 [ 6 , 7 , 8 ].…”
Section: Discussionsupporting
confidence: 94%
“…These data are consistent with previous reports [ 6 , 7 , 8 , 9 ]. However, in contrast to previous studies, sex was not found to be significantly associated with vaccination status Table 4 [ 6 , 7 , 8 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Notre étude concerne une population n'ayant pas de motif de consultation en rapport avec la vaccination contrairement aux études publiées. En 2006, Goirand et al dans une étude télépho-nique auprès de médecins et portant sur plus de 4 000 patients a montré que le statut vaccinal est le plus souvent apprécié par les données de l'interrogatoire devant l'absence de justificatifs médicaux et d'informations dans les dossiers médicaux [28]. Notre étude souligne l'intérêt d'améliorer la connaissance du statut vaccinal.…”
Section: Activités à Risqueunclassified